Penerapan Data Mining Untuk Pengelompokan Bibit Sawit Yang Baik Menggunakan Metode Clustering Dengan Technic Single Linkage - Asmitra Hot D Sinamo (STMIK Budi Darma, 2019)
Seeds are products that are produced from the procurement of plant materials that can affect the achievement of production. Through this nursery stage it is expected to produce good and quality seeds. In order to achieve crop production potential, palm oil seedling management is recommended to implement a planting grouping system in the field. This grouping is intended to guarantee uniformity of plant growth. It is difficult to select the palm seed grouping strategy in helping related people to take accurate steps for the next period. facilitate the implementation of culture. Data mining is mining or discovering new information by looking for certain patterns or rules from a number of raw data, which are expected to overcome these conditions. The data mining Clustering technique used in this study is a single linkage technique. Where data in clusters is formed based on the rules of this method. Based on the trials of the system that has been made it can be concluded that the use of clustering models for palm oil seedlings can produce clustering cluster values in 2.3 and 4 quantification of the set of criteria. From the results of the study it can be concluded that the application of single linkage techniques can be used to increase crop yields. Because the data on palm oil seedlings have been separated according to the type of each seed.